112 A STUDY OF REFERRALS TO THE EMERGENCY DEPARTMENT FROM NURSING HOMES PRIOR TO AND IN THE CONTEXT OF COVID-19. (25th October 2022) - Conlon, C; Feeney, L; Drumm, B; O'Sullivan, F
Abstract: Background: As of July 2020 there were 32, 000 residential places in Ireland. In the context of Covid-19, there was a rise in attendance at Emergency Departments( ED) of those aged above seventy. The objectives were to collect data on the profile of Nursing Home (NH) residents referred to ED, establish if meeting target Patient Experience Times (PET) in ED with NH residents and to compare attendances of NH residents prior to and in the context of Covid-19. Methods: The study was performed in two phases, the first a retrospective study in June 2017 and the second an observational study in December 2021. A proforma was drawn up to collect data of interest inclusive of reason for referral, mode of referral and clinical frailty scale. The data was analyzed using SPSS. Results: The initial study included ninety charts, the second phase included twenty-six charts. In the recent study the majority were male 62% (16/26), aged 81-90 years 38% (10/26) and severely frail (Clinical Frailty Scale=7 50% 12/26). The percentage of weekend referrals remained similar with 26% and 27% of referrals on Saturday and Sunday in the initial and subsequent study respectively. Regarding medical review prior to transfer, 58% (15/26) had medical review (previously 62 %), 42% (11/26) had not (previously 38%). Of those who had a medical review 46% (7/15) were via telephone by out of hours service compared to 25%(14/56) in the initial study. PETs were greater than six hours in 73% (19/26) of cases, previously 68%. Conclusion: Overall this timely study illustrates a majority of NH residents are brought to the ED without being seen face-to-face by a General Practitioner and an increase in virtual assessments since the advent of Covid-19. It highlights how a regional hospital and the NHs it serves could benefit from a community geriatric team and will help inform service provision.